Constraints and/or determinants of return to sexual activity in the puerperium Condicionantes y/o determinantes del retorno a la actividad sexual en el puerperio Condicionantes e/ou determinantes do retorno à atividade sexual no puerpério - Cleci de Fátima Enderle; Nalú Pereira da Costa Kerber; Valéria Lerch Lunardi; Camila Magroski Goulart Nobre; Luiza Mattos; Eloisa Fonseca Rodrigues (Universidade de São Paulo, 2013)
OBJECTIVE: to identify factors which constrain or determine the return to sexual activity in the puerperium. METHOD: exploratory and descriptive study undertaken in a university hospital in the South of Brazil. Fifteen women who had recently given birth, who received a consultation with the nurse in the period August - October 2011, took part in the study. Data was collected after the consultation had finished through semi-structured interviews, in which the women who had recently given birth were asked about the return to sexual activity and the feelings involved in this process. RESULTS: the principal determinant/constraint for return to sexual activity in the post-natal period was the fear of a new pregnancy. Fear of feeling pain, permission from the health professional, shame of their own bodies and changes in libido emerged as constraining and/or determinant factors in the thematic analysis. CONCLUSION: it is considered fundamental for the issue of contraception to be addressed with the woman/couple during the pre-natal consultation, so that there may be opportunities for reflection and dialog prior to the critical time itself. OBJETIVO: identificar factores que condicionan y/o determinan el retorno de las actividades sexuales en el puerperio. MÉTODO: estudio exploratorio y descriptivo desarrollado en un hospital universitario del Sur de Brasil. Hicieron parte del estudio 15 puérperas que realizaron la consulta de enfermería, en el período de agosto a octubre de 2011. La recolección de datos aconteció por entrevista semiestructurada, después del término de la consulta, preguntándoles sobre el retorno de la actividad sexual y las sensaciones involucradas en este proceso. RESULTADOS: el miedo de un nuevo embarazo fue el principal determinante/condicionante del retorno sexual en el posparto. En el análisis temático sobresalieron como factores condicionantes y/o determinantes, el miedo de sentir dolor, la liberación del profesional de salud, la vergüenza del propio cuerpo y las alteraciones en la libido. CONCLUSÍON: se considera fundamental que la temática de la anticoncepción sea abordada con la mujer/pareja durante el prenatal, para que tenga oportunidad de reflexionar y dialogar, antes del momento crítico en sí. OBJETIVO: identificar fatores que condicionam e/ou determinam o retorno das atividades sexuais no puerpério. MÉTODO: estudo exploratório e descritivo, desenvolvido em um hospital universitário do Sul do Brasil. Fizeram parte do estudo 15 puérperas que realizaram a consulta de enfermagem, no período de agosto a outubro de 2011. A coleta de dados aconteceu por entrevista semiestruturada, após o término da consulta, questionando-as quanto ao retorno da atividade sexual e às sensações envolvidas nesse processo. RESULTADOS: o medo de uma nova gravidez foi o principal determinante/condicionante do retorno sexual no pós-parto. Na análise temática despontou, como fatores condicionantes e/ou determinantes, o medo de sentir dor, a liberação do profissional de saúde, a vergonha do próprio corpo e as alterações na libido. CONCLUSÃO: considera-se fundamental que a temática da anticoncepção seja abordada com a mulher/casal durante o pré-natal, para que tenha oportunidade de reflexão e diálogo, anterior ao momento crítico em si.